EVALUATION OF ECONOMIC EFFICIENCY OF INNOVATIVE WATER TREATMENT TECHNOLOGIES OF SWIMMING POOLS AND WATER PARKS - STRUTYNSKA, Lesya (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Typical processes of water purification and water treatment of water park pools are considered. The method of economic estimation of efficiency of their application is offered. The methodology is based on the introduction of a number of indicators of the quality of the water treatment process of calculating the coefficient of "efficiency criterion" of water treatment of swimming pools. The purpose of this study was to develop an innovative technology of electrolytic-cavitation water treatment for swimming pools and water parks and to create a method of comparative evaluation of the effectiveness of modern water treatment technologies. A new technological scheme of electrolytic-cavitation water purification of public water bodies is proposed. A mathematical dependence has been created, which allows to objectively assess the effectiveness of various methods of water treatment and purification using the proposed indicator called "efficiency criterion" It is established that the proposed method of electrolytic-cavitation water purification has the highest values ​​of efficiency from the considered water purification processes. This method is based on an organic combination of the advantages of such physical methods as electrolytic and cavitation disinfection of organic and biological water pollutants. The degree of purification and disinfection provided by him reaches 97-98%.